Legacy System Modernization: Strategic Imperatives and Transformation Metrics in Digital Evolution - Sasidhar Reddy Somula (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Legacy system modernization has emerged as a critical imperative in today’s digital transformation landscape, presenting organizations with complex challenges that span technical, operational, and human dimensions. This article examines the multifaceted aspects of legacy modernization, focusing on strategic approaches, performance considerations, and implementation methodologies. The article explores how organizations can effectively balance the preservation of critical system reliability with the introduction of modern capabilities such as cloud computing, artificial intelligence, and advanced analytics. Through analysis of European public administration cases and industry research, this article investigates the interplay between technical architecture, user experience, change management, and value delivery. The article demonstrates that successful modernization initiatives require a carefully orchestrated approach that combines phased implementation strategies, comprehensive stakeholder management, and innovative technology integration. This article provides insights into effective modernization frameworks, highlighting the importance of balancing immediate operational needs with long-term strategic objectives while maintaining system stability throughout the transformation journey.